2018
DOI: 10.1037/xhp0000443
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory coarticulation and the minimal planning unit of speech.

Abstract: One of the most persistent arguments against the segment as the minimal planning unit is that the seemingly ubiquitous, thus, presumed obligatory, nature of anticipatory coarticulation (AC) effects favors the syllable or a larger unit. By contrast, we present the results of 3 experiments showing that AC is not ubiquitous, but graded and variable based on (a) phonological availability and (b) the specific criterion to initiate articulation adopted by a speaker. We further argue that phonological encoding is par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…This is also consistent with a large body of work demonstrating that some aspects of coarticulation are pervasive and intrinsic to speech production and perception (Fowler & Saltzman, 1993;Goldstein & Fowler, 2003;Liberman, Cooper, Shankweiler & Studdert-Kennedy, 1967). However, Liu, Kawamoto, Payne, and Dorsey (2018) showed that some aspects of anticipatory coarticulation may be gradient in scope and degree, depending on the availability of information about an utterance, and speakers' approach to the task. Furthermore, in some circumstances, speech movements can be dissociated from higherlevel linguistic units: individual speech movements can be initiated before other movements involved in producing the same segment or syllable (Tilsen, Spincemaille, et al 2016), or halted before completion (Ladefoged, Silverstein, & Papçun, 1973;Tilsen & Goldstein, 2012).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is also consistent with a large body of work demonstrating that some aspects of coarticulation are pervasive and intrinsic to speech production and perception (Fowler & Saltzman, 1993;Goldstein & Fowler, 2003;Liberman, Cooper, Shankweiler & Studdert-Kennedy, 1967). However, Liu, Kawamoto, Payne, and Dorsey (2018) showed that some aspects of anticipatory coarticulation may be gradient in scope and degree, depending on the availability of information about an utterance, and speakers' approach to the task. Furthermore, in some circumstances, speech movements can be dissociated from higherlevel linguistic units: individual speech movements can be initiated before other movements involved in producing the same segment or syllable (Tilsen, Spincemaille, et al 2016), or halted before completion (Ladefoged, Silverstein, & Papçun, 1973;Tilsen & Goldstein, 2012).…”
Section: Introductionsupporting
confidence: 88%
“…Furthermore, in some circumstances, speech movements can be dissociated from higherlevel linguistic units: individual speech movements can be initiated before other movements involved in producing the same segment or syllable (Tilsen, Spincemaille, et al 2016), or halted before completion (Ladefoged, Silverstein, & Papçun, 1973;Tilsen & Goldstein, 2012). Speakers vary in how and how much they demonstrate preparatory articulation when information is available which facilitates anticipatory coarticulation (Liu et al, 2018;Tilsen et al, 2016), but these findings are inconsistent with models of speech production in which all aspects of speech timing and implementation are pre-organized entirely at the level of the segment or syllable.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, one could object that coarticulation might be optional between syllables but not within them. Liu, Kawamoto, Payne, and Dorsey (2018) conceptually replicated Whalen's (1990) findings within monosyllabic words. All words began with the sibilant /s/.…”
Section: Coarticulation Re‐revisitedmentioning
confidence: 57%
“…Speakers flexibly accommodate to changing circumstances by controlling the flow of articulation in real time. We see evidence for this not only in anticipatory posturing during delayed naming (Kawamoto et al, 2008; Tilsen et al, 2016), but in variable manifestation of coarticulation (Liu et al, 2018), and local warping of the articulatory and acoustic time course (e.g., Kawamoto et al, 2014).…”
Section: So What?mentioning
confidence: 74%
“…Linguistic and speech production models have postulated syllables as a programming unit (e.g., Levelt et al, 1999;Cholin et al, 2006). However, there is also significant evidence to suggest smaller programming units, e.g., phonemes, may influence speech production more overtly (e.g., Meigh, 2017;Liu et al, 2018;Meigh et al, 2018). These different interpretations influence the construction of stimuli and the variables controlled across stimuli sets in experimental studies of speech motor learning.…”
Section: Introductionmentioning
confidence: 99%